2014
DOI: 10.1002/ange.201400807
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Domino Reaction of Two Aryl Iodides Involving Two CH Functionalizations

Abstract: A palladium‐catalyzed intermolecular cross‐coupling of two aryl iodides is reported, giving polycyclic ring systems with a high level of convergence and efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Communications to the formation of spirocyclic product 6 in 63 %y ield (Scheme 3a). Based on literature precedents, [5][6][7][8][9]13] this outcome implies that the reaction proceeds via cyclopalladation to form the key intermediate II,f ollowed by intermolecular biaryl coupling involving Pd IV -species III,with termination by dearomative spiroannulation of IV.T he assumed mechanism was further supported by the reaction performance between 1aand 7 (Scheme 3b). Theoutcome of this reaction indicated that:1)Pd IV species III' ',which is like III,was involved as the intermediate;2 )reductive elimination of III' ' and the subsequent C À Harylation took place via two pathways.Moreover, at hree-component control reaction (Scheme 3c)r evealed that an alkyne tethered on the aryl iodide partner was crucial for the intermolecular cross-coupling of such two different aryl halides.…”
Section: Angewandte Chemiementioning
confidence: 82%
See 1 more Smart Citation
“…Communications to the formation of spirocyclic product 6 in 63 %y ield (Scheme 3a). Based on literature precedents, [5][6][7][8][9]13] this outcome implies that the reaction proceeds via cyclopalladation to form the key intermediate II,f ollowed by intermolecular biaryl coupling involving Pd IV -species III,with termination by dearomative spiroannulation of IV.T he assumed mechanism was further supported by the reaction performance between 1aand 7 (Scheme 3b). Theoutcome of this reaction indicated that:1)Pd IV species III' ',which is like III,was involved as the intermediate;2 )reductive elimination of III' ' and the subsequent C À Harylation took place via two pathways.Moreover, at hree-component control reaction (Scheme 3c)r evealed that an alkyne tethered on the aryl iodide partner was crucial for the intermolecular cross-coupling of such two different aryl halides.…”
Section: Angewandte Chemiementioning
confidence: 82%
“…[8,9] In connection with our interest in metal-catalyzed dearomatization reactions, [10,11] we recently reported a[ 2 + +2+ +1] spiroannulation of 1-bromo-2-naphthols with aryl iodides and alkynes that relies on the electron-rich palladacycle A (Scheme 1b). [12] Notably,o ne main obstacle for optimization was homo-coupling of aryl iodides.I nspired by the alkenetethered strategy for cross-coupling of different aryl iodides, [13] we initiated further trials with an alkene-tethered aryl iodide,offering apalladacycle A' ',which is similar to A,to react with 1-bromo-2-naphthol (Scheme 1c). However, the reaction didntp roceed well, since it was difficult to avoid homo-coupling of aryl iodides (see Table S1 in the Supporting Information).…”
mentioning
confidence: 99%
“…Notably, one main obstacle for optimization was homo‐coupling of aryl iodides. Inspired by the alkene‐tethered strategy for cross‐coupling of different aryl iodides, we initiated further trials with an alkene‐tethered aryl iodide, offering a palladacycle A′ , which is similar to A , to react with 1‐bromo‐2‐naphthol (Scheme c). However, the reaction didn't proceed well, since it was difficult to avoid homo‐coupling of aryl iodides (see Table S1 in the Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Reacting complex I , which was generated from 1 a by intramolecular carbopalladation, with an equal amount of aryl bromide 5 led to the formation of spirocyclic product 6 in 63 % yield (Scheme a). Based on literature precedents, this outcome implies that the reaction proceeds via cyclopalladation to form the key intermediate II , followed by intermolecular biaryl coupling involving Pd IV ‐species III , with termination by dearomative spiroannulation of IV . The assumed mechanism was further supported by the reaction performance between 1 a and 7 (Scheme b).…”
Section: Methodsmentioning
confidence: 99%
“…[5] Despite the remarkable progress made in this field, selective functionalization remains achallenge.Inthis regard, the application of C À Hfunctionalization in adomino process has extended the versatility and applicability of the reaction since it enables the metal center to interact with remote bonds that may otherwise be unreactive. [6][7][8][9][10] By employing this approach, we present anovel Pd-catalyzed spirocyclization reaction.…”
Section: Palladium-catalyzed Spirocyclizationthrough C à Hactivation mentioning
confidence: 99%